Revolutionizing Passport Services with M-Passport: Towards Agile and Digital Government (Agile Governance and Innovation Measurement Journal, 2024)
A passport is an essential requirement for someone who wants to travel to another country, and this passport will continue to be needed by people from time to time. However, passport processing services were first done manually, and services were subject to time constraints. Therefore, the Indonesian Ministry of Law and Human Rights Directorate General of Immigration continues to innovate passport-making services to make them faster, easier, and more efficient. One of the efforts is to issue the M-Paspor application, which is a passport application service application that can be accessed easily online. With the M-Paspor application, people can apply for a new passport or a replacement passport. This research includes qualitative research with a case study approach. Data collection uses secondary data techniques, which are obtained indirectly through information available in the mass media, websites, articles, social media, and online news. The results of this study found that M-Passport is useful as an innovative, fast, and efficient service so as to create digital and agile governance.